2015
DOI: 10.1002/cbin.10520
|View full text |Cite
|
Sign up to set email alerts
|

Time‐course effect of high‐glucose‐induced reactive oxygen species on mitochondrial biogenesis and function in human renal mesangial cells

Abstract: The present study investigated the time-course effect of high-glucose-induced reactive oxygen species (ROS) on mitochondrial biogenesis and function in human renal mesangial cells and the effect of direct inhibition of ROS on mitochondria. The cells were cultured for 1, 4, and 7 days in normal glucose or high glucose in the presence and absence of Mn(III)tetrakis(4-benzoic acid)porphyrin chloride (MnTBAP) or catalase. Mitochondrial ROS production was assessed by confocal microscope. mtDNA copy number and perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 42 publications
(82 reference statements)
0
29
0
Order By: Relevance
“…Redox agents such as H 2 S decreased TFAM promoter methylation, most likely by inhibiting DNMT3A expression, thereby maintaining mtDNA copy numbers in vascular cells (Li and Yang, ). Several other studies have reported that ROS can elevate mtDNA copy numbers (Lee and Wei, ; Hori et al , ; Marine et al , ), although this effect may be time‐ and dose‐dependent (Al‐Kafaji et al , ) and possibly also dependent on the type of redox modulation. For example, in mice exposed to cigarette smoke extracts, TFAM promoter methylation was increased resulting in strongly reduced TFAM expression and endothelial cell apoptosis (Zhang et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 96%
“…Redox agents such as H 2 S decreased TFAM promoter methylation, most likely by inhibiting DNMT3A expression, thereby maintaining mtDNA copy numbers in vascular cells (Li and Yang, ). Several other studies have reported that ROS can elevate mtDNA copy numbers (Lee and Wei, ; Hori et al , ; Marine et al , ), although this effect may be time‐ and dose‐dependent (Al‐Kafaji et al , ) and possibly also dependent on the type of redox modulation. For example, in mice exposed to cigarette smoke extracts, TFAM promoter methylation was increased resulting in strongly reduced TFAM expression and endothelial cell apoptosis (Zhang et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 96%
“…qPCR was performed with a 7900HT real-time PCR system (Applied Biosystems; Thermo Fisher Scientific, Inc.) using the following cycling conditions: 1 cycle of 50˚C for 2 min, 1 cycle of 95˚C for 10 min, and 30 cycles of 95˚C for 15 sec and 60˚C for 1 min. For each PCR run, standard curves were established from 5 serially diluted, purified PCR products (1x10 2 to 1x10 7 ng/ml) from the CYTB gene and the B2M gene to generate quantification data as previously described (19,21). Quantification of mtDNA was accomplished by calculating the ratio of mtDNA-encoded CYTB gene to the nDNA-encoded B2M gene and mtDNA-CN data were expressed as mtDNA per nDNA.…”
Section: Study Populationmentioning
confidence: 99%
“…Compared to nuclear DNA (nDNA), mtDNA is more susceptible to oxidative stress due to its close proximity to the site of free radical generation (17). Increased oxidative stress in human cells may contribute to alterations in the mtDNA-CN, mtDNA-encoded gene expression and mitochondrial abundance (18)(19)(20)(21). A previous study by our group has indicated that in response to high glucose-induced chronic oxidative stress, the renal mtDNA-CN is decreased and the mitochondria are impaired (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxygen species (ROS) have been revealed as important signaling molecules that mediate renal injury in patients with diabetes (1). High glucose (HG) increases intracellular ROS levels in renal cells and contributes to the development and progression of diabetic renal injury (2,3). Under normal physiological conditions, low levels of ROS are produced by the nicotinamide adenine dinucleotide phosphate-oxidase (NADPH) oxidase (Nox) family as byproducts of the mitochondrial electron transport chain, and are important in the regulation of various cellular functions including inflammatory gene expression, proliferation and apoptosis (4).…”
Section: Introductionmentioning
confidence: 99%